Like our foremothers survived: Self-education, direct confrontation, and humor as resistance coping in Black womxn and femme college student being - Luney, LeAnna T. (Frontiers in Education, 2022)
In our continued study of Blackness and Being, we must emphasize the quotidian – or everyday – strategies that young Black womxn and femmes employ to cope with anti-Black gendered racism and its psychological impact at historically and predominantly white institutions. As such, the purpose of this article is to give prominence to the resistant types of coping strategies that Black womxn and femme college students used to maintain their dignity at a predominantly white university of the American West, where the psychological aftermath of anti-Black gendered racism remains hidden under dense layers of neoliberalism, affluence, faux progressivism, and whiteness. I approach this topic from the conceptual perspective of Blackness and Being at the nexus of gender by combining discourses on the ontologies of Blackness, and Black feminist thought and epistemology. In the study that informs this article, I utilized qualitative mixed methods – one-on-one interviews, focus group interviews, and participant observation. Like our foremothers whose survival was predicated on the subtle and purposeful coping strategies they engaged, Black womxn and femme college students’ resistant coping styles were demonstrated in the everyday presence of anti-Black gendered racism. Findings reveal that Black womxn and femme undergraduate students demonstrated three main types of resistant coping when experiencing anti-Black gendered racism: 1.) self-education; 2.) direct confrontation with aggressors (e.g., racists, sexists, homophobes, elitists); and 2.) humor. I conclude with recommendations on transformative justice, monetary trusts, longitudinal data collection, and critical curriculum at historically and predominantly white educational institutions.